RETROSPECTIVE PLOT AND ITS TYPES IN UZBEK PROSE - Normamatov Farrukh Komiljon ugli (Western European Studies, 2024)
This article presents the retrospective plot used in complex works, its types, and examples of works using this genre in Uzbek literature.
Keywords: retrospective plot; chronological flashback